Method of temporary structures construction / Muhammad Azim Zaidee - Zaidee, Muhammad Azim (Universiti Teknologi MARA, Perak, 2022)
When it comes to the building construction industry, temporary structures are a common thing to be use in construction and also being used for maintenance work. This report will cover about the method of temporary structures construction that been conducted at Ajinoriki (MSG) Malaysia Sdn Bhd factory which located at Lot 10460, Jalan Kilang, Pekan Bestari Jaya, 45600 Bestari Jaya. The aim of this report is to examine the progress of constructing the temporary structures from planning until the completion of the temporary structures. This report will also talk through the problems that occurred before constructing the temporary structures and how the solution was did to overcome the problems.